Implementasi Customer Relationship Management pada Sistem Penjualan Tiket Wisata di Karacak Valley Berbasis Website - Amin, Abdusy Syakur; Septiana, Yosep; Rahayu, Sri; Farhan, Muhammad (Jurnal Algoritma, 2024)
Customer Relationship Management technology is used as a strategy to build relationships with tourists and provide better services for tourists. where Customer Relationship Management technology is a modern marketing tool for tourist attractions, one of which is the Karcak Valley tourist attraction in Garut Regency. Apart from that, many regional and non-regional tourists visit, but currently the tourism management in Karcak Valley still uses a manual system in selling tourist tickets and the majority of tourists still lack information regarding the facilities, promos, blogs and galleries at Karcak Valley tourism. This research aims to overcome this problem, by implementing Customer Relationship Management in the website-based tourist ticket sales system in Karcak Valley to make it easier for tourists to find information about facilities, promos, blogs, galleries and order tourist tickets in Karcak Valley online. The methodology used in the process of creating this system is Rational Unified Process using Unified Modeling Language modeling. The results of this research will be a tourist ticket sales system that includes features such as information about tourist destinations in the Karacak Valley, facilities, promos, blogs, galleries, ticket prices, tourist locations and can increase trust in tourists, both new and retaining tourists. old tourists who have visited the Karcak Valley tourist attraction and make it easier for tourists to order tourist tickets in the Karcak Valley via a website-based online system.